The Concept of Japanese Culture in Lean Production of the Toyota Automobile Company: Its Scientific Development and Application in Higher Education and Agriculture - Glushchenko, Valery Vladimirovich (Universitas Pendidikan Indonesia (Indonesia University of Education), 2023)
The purpose of the article is to create a scientific theory of lean production of goods and services (the theory of thrift), from the perspective of Japanese culture which is applicable in higher education and agriculture. Currently, a new technological way is being formed. One of the key concepts of this technological way will be the scientific theory of lean manufacturing, which can be created based on the analysis of the practice of lean manufacturing of the Toyota automobile company. The analysis of the directions of crisis management indicates the growing relevance of the introduction of lean manufacturing of goods and services in all new areas of activity, in particular in higher education and agriculture as a part of Japanese culture. However, fragmentary implementation of lean manufacturing ideas can be inefficient. This necessitates the development of the concept and content of the general theory of lean production of goods and services in higher education and agriculture. The article describes the functions, roles, and structural elements of the general theory of lean production of goods and services, a conceptual approach to the introduction of lean production of goods and services in higher education and agriculture as a part of Japanese culture is being formed.